Probe-integrated electrochemical immunosensor based on electrostatic nanocage array for reagentless and sensitive detection of tumor biomarker - Chen, Dong; Luo, Xuan; Xi, Fengna (Frontiers in Chemistry, 2023)
Sensitive detection of tumor biomarkers is crucial for early diagnosis and prognosis evaluation of cancer. Owing to no need of labelled antibody, formation of sandwich immunocomplexes and additional solution-based probe, probe-integrated electrochemical immunosensor for reagentless detection of tumor biomarkers is highly desirable. In this work, sensitive and reagentless detection of a tumor biomarker is realized based on fabrication of a probe-integrated immunosensor by confining redox probe in electrostatic nanocage array modified electrode. Indium tin oxide (ITO) electrode is employed as the supporting electrode because it is cheap and easily available. The silica nanochannel array consisted of two layers with opposite charges or different pore diameters was designated as bipolar films (bp-SNA). In this work, Electrostatic nanocage array is equipped on ITO electrode by growth of bp-SNA with two layered nanochannel array having different charge properties including a negatively charged silica nanochannel array (n-SNA) and a positively charged amino-modified SNA (p-SNA). Each SNA can be easily grown with 15 s using electrochemical assisted self-assembly method (EASA). Methylene blue (MB) is applied as the model electrochemical probe with positive charge to be confined in electrostatic nanocage array with stirring. The combination of the electrostatic attraction from n-SNA and the electrostatic repulsion from p-SNA endows MB with highly stable electrochemical signal during continuous scanning. When the amino groups of p-SNA are modified using the bifunctional glutaraldehyde (GA) to introduce aldehydes, the recognitive antibody (Ab) of the most commonly used tumor biomarker, carcinoembryonic antigen (CEA), can be covalently immobilized. After the non-specific sites are blocked, the immunosensor is successfully fabricated. As the formation of antigen-antibody complex decreases electrochemical signal, the immunosensor can achieve reagentless detection of CEA ranged from 10 pg/mL to 100 ng/mL with a low limit of detection (LOD, 4 pg/mL). Determination of CEA in human serum samples is realized with high accuracy.